SUSTAINABILITY OF TEMANGGUNG COFFEE FARMING SYSTEM IN THE PERSPECTIVE OF GEOGRAPHICAL INDICATIONS - I Ketut Ardana (Jurnal Penelitian Tanaman Industri, 2019)
Geographical Indications (GIs) certificate is required to protect specific flavors of crops in the given region. The study aimed to analyze the sustainability of the coffee farming system basis of Sindoro-Sumbing Java Arabica Coffee and Temanggung Robusta Coffee from the perspective of GIs protection. The study used survey methods with data collection techniques: (1) literature studies, interviews, and discussions with stakeholders, and (2) observation of the application of coffee cultivation and processing. The analytical methods used were (1) analysis of technical and institutional performance, and economic benefits with cross-tabulation and descriptive interpretation, and (2) analysis of the sustainability of coffee farming system using a multidimensional scaling approach. The results showed that the management of coffee farming in the Temanggung Regency was quite sustainable from the perspective of GIs protection with an index value of 66.88. The six dimensions of sustainability, showing fairly sustainable performance with an index of 59.22-74.99. This indicated that a comprehensive improvement is required to sustain the GI protection in Temanggung Regency, i.e., ecology, economy, ethics, institutions, social, and technology. Sensitive lever factors to improve the performance of each dimension are (1) adaptation to climate influence, land conservation, and cropping patterns for ecological dimensions, (2) commodity alternatives and price stability for economic dimensions, (3) logo inclusion on packaging, environmental maintenance, and the authenticity of products for ethical dimensions, (4) optimizing the role of GIPC for institutional dimensions, (5) involvement of stakeholders in the social dimension, and (6) improvements in harvesting methods for technological dimensions.Keywords:   Lever factors, arabica coffee, robusta coffee AbstrakSertifikat Indikasi Geografis (GI) diperlukan untuk melindungi rasa tanaman tertentu di wilayah tertentu. Penelitian ini dilakukan dari bulan Desember 2017 hingga Mei 2018, bertujuan untuk menganalisis keberlanjutan usahatani kopi Arabika Java Sindoro-Sumbing dan Kopi Robusta Temanggung dalam perspektif perlindungan IG menggunakan metode survei dengan teknik pengumpulan data: (1) studi pustaka, wawancara dan diskusi dengan pemangku kepentingan, dan (2) observasi penerapan budidaya dan pengolahan kopi. Metode analisis yang digunakan meliputi: (1) Analisis kinerja teknis,  kelembagaan, dan manfaat ekonomi dengan tabulasi silang dan interpretasi secara deskriptif, dan (2) Analisis keberlanjutan menggunakan pendekatan multidimensional scaling. Hasil penelitian menunjukkan bahwa pengelolaan usahatani kopi di Kabupaten Temanggung cukup berkelanjutan dari perspektif perlindungan IG dengan nilai indeks 66,88. Keenam dimensi keberlanjutan, menunjukkan kinerja cukup berkelanjutan dengan indeks 59,22-74,99 mengindikasikan bahwa untuk meningkatkan keberlanjutan perlindungan IG kopi di Kabupaten Temanggung masih perlu perbaikan pada dimensi ekologi, ekonomi, etika, kelembagaan, sosial, dan teknologi. Faktor pengungkit yang sensitif untuk memperbaiki kinerja masing-masing dimensi adalah: (1) adaptasi terhadap pengaruh iklim, konservasi lahan, dan pola tanam untuk dimensi ekologi, (2) alternatif komoditas dan stabilitas harga untuk dimensi ekonomi, (3) pencantuman logo pada kemasan, mitigasi lingkungan, dan keaslian produk untuk dimensi etika, (4) mengoptimalkan peran MPIG untuk dimensi kelembagaan, (5) soliditas komunitas “Sahabat Kopi” dan keterlibatan stakeholder untuk dimensi sosial, serta (6) perbaikan cara panen untuk dimensi teknologi.Kata kunci: faktor pengungkit, keberlanjutan, kopi arabika, kopi robusta, indikasi geografis.